2020
DOI: 10.5114/polp.2020.97102
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Ukrainian version of the PedsQLTM 4.0 Generic Core Scales in children and adolescents with vasovagal syncope

Abstract: Introduction: The aim of the study was to assess the psychometric properties of the Ukrainian translation of the PedsQL™ 4.0 Generic Core Scales for Ukrainian children and adolescents with vasovagal syncope, as well as to study health-related quality of life in this group of paediatric patients. Materials and methods: We studied 56 children, aged eight to 17 years, with a history of vasovagal syncope, and 41 healthy volunteers. Health-related quality of life assessment was performed using the Ukrainian version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
5
0
3
Order By: Relevance
“…Individual study results, including baseline quality of life scores, between-group comparisons and additional contextual findings are reported in Table 2. To avoid redundancy in our reporting, data from three longitudinal studies (26,35,36) have been omitted from Table 2; their results, including baseline scores, comparisons and contextual findings can be found in Table 3. We note that these three studies report follow-up data from three prior studies that are described in Table 2 (26,41,42).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual study results, including baseline quality of life scores, between-group comparisons and additional contextual findings are reported in Table 2. To avoid redundancy in our reporting, data from three longitudinal studies (26,35,36) have been omitted from Table 2; their results, including baseline scores, comparisons and contextual findings can be found in Table 3. We note that these three studies report follow-up data from three prior studies that are described in Table 2 (26,41,42).…”
Section: Resultsmentioning
confidence: 99%
“…VAS (EQ VAS or global health) scores were significantly reduced in VVS, POTS, and OH patient populations ( 10 , 49 , 54 ), and EQ-5D-3L index scores were additionally found to be reduced in patients with OH ( 54 ). Two studies showed that total PedsQL scores (child self-reported) were significantly reduced in children with VVS compared to healthy controls ( 8 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Хронічні захворювання дитячого віку, включно з ТВС, обумовлюють суттєві зміни у всіх сферах життя дитини -у повсякденних справах, емоційному та когнітивному розвитку, формуванні самооцінки та соціальних контактів із іншими людьми [3, [10][11][12]. Це дослідження було змодельоване таким чином, щоб вивчити вплив епілепсії, ПНЕН та психогенних ТВС на особливості якості життя дітей та функціонування їхніх сімей.…”
Section: обговоренняunclassified
“…До того ж визначення якості життя дітей і надалі залишається важливим інструментом оцінки якості надання медичних послуг [7]. Станом на сьогодні є чимало досліджень, які доводять негативний вплив транзиторних втрат свідомості (ТВС) синкопального походження на показники якості життя дітей, пов'язаної зі здоров'ям [8][9][10]. Доведено, що погіршення якості життя у педіатричних пацієнтів із епілепсією як проявом ТВС несинкопального походження асоціюється з тривалістю захворювання та частотою судом, необхідністю використання кількох протисудомних препаратів [11].…”
unclassified